2019
DOI: 10.1097/md.0000000000015512
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of both human menopausal gonadotropin (HMG) and recombinant luteinizing hormone addition at early follicular stage in in vitro fertilization outcome

Abstract: At present, the precise role of human menopausal gonadotropin (HMG) and recombinant luteinizing hormone (rLH) supplementation at an early time of follicular phase on in vitro fertilization (IVF)/intra cytoplasmatic sperm injection (ICSI) outcomes remains uncertain. Here infertile women of normal ovarian function undergoing their first cycle of IVF/ICSI were studied and were randomly allocated into 3 groups. Group 1, ovarian stimulation with 150IU recombinant follicle-stimulating hormone (FSH) alone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…A previous study obtained a similar conclusion in women > 35 y [26]; the ongoing pregnancy rate was higher in an rFSH + rLH group than that in an hMG group (17.3% vs. 12.2%). However, in another study, the supplementation of LH did not show any signi cant improvement in clinical outcomes [27]. There should be differences in effectiveness between HCG and rLH based on their mechanism of action, thus we propose that the inconsistency of the effectiveness of rLH supplementation is related to the extent of decrease in LH.…”
Section: Discussionmentioning
confidence: 65%
“…A previous study obtained a similar conclusion in women > 35 y [26]; the ongoing pregnancy rate was higher in an rFSH + rLH group than that in an hMG group (17.3% vs. 12.2%). However, in another study, the supplementation of LH did not show any signi cant improvement in clinical outcomes [27]. There should be differences in effectiveness between HCG and rLH based on their mechanism of action, thus we propose that the inconsistency of the effectiveness of rLH supplementation is related to the extent of decrease in LH.…”
Section: Discussionmentioning
confidence: 65%
“…The search yielded 11 articles, of which three were prospective trials (Pacchiarotti et al, 2010;Requena et al, 2014;Tehraninejad et al, 2017): two were randomized controlled trials (Pacchiarotti et al, 2010;Tehraninejad et al, 2017) and one was a prospective observational study, in which patients were assigned to each treatment group based on a quasi-experimental design comprising consecutive opportunity sampling (Requena et al, 2014). Eight retrospective studies were found (Buhler and Fischer, 2012;Fábregues et al, 2013;Dahan et al, 2014;Revelli et al, 2015;Schwarze et al, 2016;Bleau et al, 2017;Renzini et al, 2017;Xia et al, 2019). The characteristics of all the studies are presented in TABLE 1.…”
Section: Resultsmentioning
confidence: 99%
“…The studies used different ovarian stimulation protocols (TABLE 1): long GnRH-agonist (Pacchiarotti et al, 2010;Buhler and Fischer, 2012;Fábregues et al, 2013;Requena et al, 2014;Bleau et al, 2017;Renzini et al, 2017;Tehraninejad et al, 2017;Xia et al, 2019), GnRH-antagonist (Schwarze et al, 2016), both (Revelli et al, 2015), or long GnRH-agonist and microdose flair GnRH-agonist (Dahan et al, 2014). Considering the type and source of gonadotrophin preparations, eight used HMG (Pacchiarotti et al, 2010;Buhler and Fischer, 2012;Dahan et al, 2014;Revelli et al, 2015., Schwarze et al, 2016Bleau et al, 2017;Tehraninejad et al, 2017;Xia et al, 2019) and three used HP-HMG (Fábregues et al, 2013;Requena et al, 2014;Renzini et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations